Penggunaan 3 Kata Sakti, Perilaku Sebab Akibat Pada Peserta Didik Kelas V SDN 1 Pucungkidul - Rahmanda Agustiningtyas, Hepi; Yasip, Yasip (Jurnal Pendidikan Tambusai, 2023)
The Importance of the Habituation Method of SayingSorry, please, In the world of education, every child hasdifferent potential in behaving and behaving properly andcorrectly. The formulation of the problem in this study "Howis the formation of children’s character in providing anunderstanding of the behavior of using 3 magic words (sorry,please, thank you) for fifth grade students at SDN 1 PucungKidul, Boyolangu Tulungagung?" with the aim of research todescribe the formation of children’s character in providing anunderstanding of the behavior of using 3 magic words (sorry,please, thank you) in class V students at SDN 1 PucungKidul, Boyolangu Tulungagung. This research is a type ofdescriptive research using a qualitative approach, which isdata relating to facts, circumstances, variables andphenomena that occur when the research takes place andpresents what it is. The subject of this research is the fifth-grade students of SDN 1 Pucungkidul. The researchinstrument used observation sheets and interview sheets. Inthe stage of providing information and motivation(Orientation), Identification Stage (Analysis) Givinghabituation carried out by the teacher is carried out naturallybecause the teacher is well acquainted with the attitude andpersonality of the fifth-grade students at SDN 1 PucungKidul.